Search for a heavy gauge boson decaying to a charged lepton and a neutrino in 1 fb-1 of pp collisions at √s = 7 TeV using the ATLAS detector - Anduaga, Xabier Sebastián (2011)
The ATLAS detector at the LHC is used to search for high-mass states, such as heavy charged gauge bosons (W'), decaying to a charged lepton (electron or muon) and a neutrino. Results are presented based on the analysis of pp collisions at a center-of-mass energy of 7 TeV corresponding to an integrated luminosity of 1.04 fb-1. No excess above Standard Model expectations is observed. A W' with Sequential Standard Model couplings is excluded at the 95% confidence level for masses up to 2.15 TeV.